Book Review Evangelicals Engaging in Practical Theology: Theology that Impacts the Church and World Edited by Helen Morris and Helen Cameron Abingdon: Routledge, 2022 pp 268, hb, ISBN 9780367545109,. (2022) - Strand, Sarah
No abstract available